Emergency Notification Apps as Embodied Responsibilization - Ribak, Rivka (AoIR Selected Papers of Internet Research, 2026)
The paper explores the emergency notification app, developed in order to alert individuals to immediate danger while preserving the resilience of the home front as a whole. Drawing on walkthroughs of emergency apps and an analysis of related materials, I suggest how this disruption not only manifests in but also enables three interrelated processes: the dissolution of the national collective into individually-alerted users; the blurring of the distinction between emergency and routine; and the delegation of preparedness responsibility from the state to individual users. I argue that these three processes – facilitated by the seemingly life-saving, deeply personalized disruption of the emergency app – carry critical political consequences. By creating an illusion of personal safety, these processes, which materialize in the hand-held disruption app, allow for a prolonged state of exception and the indefinite protraction of war and danger.